Elektrische apparaten van de ‘Nederlandsche Optiek- en Instrumentenfabriek Dr. C.E. Bleeker’ - Ruitenbeek, Kees (Studium, 2015)
Bleeker’s Electrical Instruments Mrs. Dr. C.E. Bleeker (1897–1985) led a company in optical and electrical instruments since 1932. While her optical instruments – including Prof. Frits Zernike’s Nobel Prize-winning phase contrast microscope – are well known, she also made a name in electrical devices. In addition to a series of highly accurate resistors – normal resistors, precision resistors and resistor banks – a range of electrical instruments were developed, such as Wheatstone bridges and compensators. In 1963, Dr Bleeker retired, but her firm continued until 1978, when nearly all activities ceased. Only the interests in Bleeker’s range of resistors continued. The current manufacturer still refers to ‘Bleeker’s principle’ in rela- tion to the quality of the resistors.